Land Deed Officials Responsibility for Sale and Purchase Deeds That Made Unlawfully (Review Decision of Wonogiri State Court Number 13/PDT.G/2021/PN Wng) - Lorraine Anggi Taruli Hutagalung; R. Rahaditya (Eduvest - Journal of Universal Studies, 2023)
This study aims to discusses the Land Deed Officials (PPAT) which has the authority to issue/ issue authentic deeds for the parties, especially in the process of transferring land rights through buying and selling, where authentic deeds have perfect evidentiary power. However, in the case that the authors discuss below, there is an abuse of authority in carrying out their duties as a PPAT. The PPAT in carrying out its duties in the form of making authentic deeds must be carried out carefully and thoroughly. The responsibility of the PPAT for the cancellation of the sale and purchase deed due to an unlawful act in the Wonogiri District Court Decision Number 13/PDT.G/2021/PN Wng., in the decision it is explained that the PPAT has violated the law as a result of not fulfilling the legal terms of the agreement in Article 1320 of the Civil Code. This type of research is normative juridical, using qualitative data analysis methods, while to examine legal problems, primary legal materials, secondary legal materials, and tertiary legal materials are used, which are then analyzed descriptively analytically.The consequence of a sale and purchase deed that is null and void because it contains legal defects is that the AJB is considered to be null and void or has never existed so that all legal actions related to the AJB are null and void and have no legal force.